An autonomous GPS geofence alert system to curtail avian fatalities at wind farms. Issue 1 (December 2015) - Sheppard, James; McGann, Andrew; Lanzone, Michael; Swaisgood, Ronald
Abstract Background Wind energy developments are increasingly proliferating as nations seek to secure clean and renewable energy supplies. Wind farms have serious impacts on avifauna populations through injuries sustained by collisions with turbines. Our aim was to develop new biotelemetric technologies to minimize collision risks, particularly for threatened and endangered bird species whose ranges overlap with current and future wind farm sites. Results We report on the development and application of an autonomous alert system that successfully miniaturizes and integrates virtual geofence capability into solar-powered biotelemetry devices used to track species of large birds currently impacted by wind farms, such as cranes and raptors. These units combine a GPS receiver with a GSM communications system that transmits acquired high-resolution location data via cellular networks in near real-time. Custom sized geofences can be placed around wind farms. When a telemetered bird ingresses one of these virtual boundaries the GPS location fix rate decreases from 15-min to 30 s and an SMS alert is automatically transmitted to a user group within 2-min. When the bird egresses the geofence zone, a second alert is sent and the fix rate returns to 15-min to conserve transmitter energy and data acquisition costs. Conclusions Combining GPS level accuracy, a high fix sampling rate, location data received in near real-time, and automated SMS alerts into an integrated, flexible and cost-effective geofence biotelemetry system will provide conservation managers and wind farm operators with sufficient warning and time to implement mitigative actions to curtail avian collision fatalities.